DEVELOPING SPEAKING SKILL THROUGH ORAL DESCRIPTION PRACTICE - Bunga Nida Azhari (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
When This study entitled â€œDeveloping Speaking Skill Through Oral Description Practiceâ€. It was focused on studentsâ€™ speaking ability through oral description practice in one of Senior High School in Garut. The participants of this study consisted of one class of the second grade, 30 students. To achieve the purpose, this study used pre-experimental design. This study aimed to find out the effectiveness of oral description practice in improving studentsâ€™ speaking ability. Pre-test and post-test were employed to obtain the data. Based on the result from the pre-test and post-test that the average scores of pre-test was 70.27. After giving the treatments, the average of post-test was 74.13. The minimum standard value in English speaking skill based on lesson plan is 70. According to the post-test data lot of studentâ€™ got score more than 70. Based on the hypothesis tested, it could be concluded that Ha could be accepted if there was a significant improvement in studentsâ€™ speaking ability by using oral description practice. The testing was showed that t observed = 7.1178 was placed in the area where Ha was accepted. Thus, it means that Ha is accepted otherwise Ho is rejected. So, there was a significant influence oral description practice in improving studentsâ€™ speaking ability.